2002
DOI: 10.1007/s004020100324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of femoral head osteonecrosis using three-dimensional finite element method

Abstract: A three-dimensional finite element model of a femoral head was developed using a surface modeling technique. The distribution of the stress index S (S = effective stress / yield strength, sigma/sigmaY) in various sizes of segmental osteonecrosis was assessed. The stress index of the femoral head was within physiological limits when the necrotic angle was less than 110 degrees. Within both the subchondral region and the deep necrotic region adjacent to the necrotic-viable interface, values of the stress index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…transtrochanteric rotational osteotomy (Lee et al 2006), bone grafting (Brown et al 1993Penix et al 1983;Lian et al 2008), intertrochanteric osteotomy (Baker et al 1989), prediction of femoral head collapse (Volokh et al 2006) or solely stress analyses of necrotic femoral heads (Yang et al 2002). None of these papers address the risk of subtrochanteric fractures after surgery or even analyze the long-term success.…”
mentioning
confidence: 97%
“…transtrochanteric rotational osteotomy (Lee et al 2006), bone grafting (Brown et al 1993Penix et al 1983;Lian et al 2008), intertrochanteric osteotomy (Baker et al 1989), prediction of femoral head collapse (Volokh et al 2006) or solely stress analyses of necrotic femoral heads (Yang et al 2002). None of these papers address the risk of subtrochanteric fractures after surgery or even analyze the long-term success.…”
mentioning
confidence: 97%
“…Type L3: the necrosis involved the three pillars including the cortical bone and marrow same area, the femoral head would collapse in the end. Yang pointed out that the yield stress of necrotic bone is 5.5 MPa, the stress index is 0.1, and the critical stress of collapse is 0.55 MPa [14]. In this study, the peak von Mises stresses of the necrosis areas in type M, C, and L1 ONFH models were 0.22 MPa, 0.43 MPa, and 0.44 MPa, respectively, which did not exceed the critical stress.…”
Section: Discussionmentioning
confidence: 49%
“…Some studies have expounded the femoral head collapse from biological factors or mechanical factors. Yang pointed out that biomechanical base of the femoral head collapse was a combined result of poor function condition of internal structure of osteonecrosis, the elastic modulus of the necrotic bone, and the yield strength [14]. However, many studies have reported that type L2 and L3 ONFH patients had poor prognoses and treatment effects in combination with numerous clinical follow-up data, up until now, the causes of collapse have not been completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations